Employment as the Missing Link: Full Mediation of Minimum Wage Effect on Per Capita Income in Central Java - Pratista, Regina; Istiqomah, Istiqomah; Pravitasari, Chairani Fadhila (Signifikan: Jurnal Ilmu Ekonomi, 2025)
Research Originality: This paper is original by explicitly analyzing employment as a mediating variable in the relationship between minimum wage and per capita income, given the inconclusive findings of previous research on these variables. Research Objectives: This study investigates the relationship between minimum wage and per capita income and examines the mediating role of employment with two control variables: government expenditure and education. Research Methods: This study utilized secondary data from BPS covering 35 districts and municipalities in Central Java Province over the period 2018–2023. The study applies panel-data regression, complemented by mediation analysis using path analysis and the Sobel test. Empirical Results: The minimum wage does not directly affect per capita income; instead, its impact is fully mediated by employment. The finding suggests that the minimum wage alone does not raise per capita income; rather, it exerts its influence indirectly by improving employment, which in turn drives income growth. As control variables, government expenditure and education exert positive and significant effects on per capita income. Implications: A minimum wage policy must be accompanied by job-creation strategies. A minimum wage increase without policies that maintain or increase jobs will not effectively boost per capita income. JEL Classification: E24, H52, J31, O15 How to Cite:Pratista, R., Istiqomah., & Pravitasari, C. F. (2025). Employment as the Missing Link: Full Mediation of Minimum Wage Effect on per Capita Income in Central Java. Signifikan: Jurnal Ilmu Ekonomi, 14(2), 437-448. https://doi.org/10.15408/sjie.v14i2.46419.